Development of Podcast as a Learning Medium at Senior High School to Build Students’ Critical Historical Thinking Skills - Insyirah, Safina; Syarifuddin, Syarifuddin; Safitri, Sani (Studies in Learning and Teaching, 2024)
This study seeks to develop a podcast medium for history education aimed at enhancing students’ historical thinking skills. Employing the Hannafin and Peck model, the research process involved needs analysis, design, development, and implementation stages. Field trial results indicated a significant improvement in students’ learning outcomes, with a 45.59% increase and a high N-gain score of 0.72. Despite the relatively low average score of 26.47 on the essay questions designed to measure their overall historical thinking skills, the students demonstrated notable proficiency in the chronological thinking aspect. The innovative side of this study primarily lies in the use of podcast as a teaching medium in history education, a method not yet widely utilized in schools, offering an engaging alternative to traditional teaching approaches. Furthermore, the podcast was created using modern technology, specifically the Dolby On application, which effectively helped our focus on developing students' historical thinking skills.